1983
DOI: 10.1136/vr.112.23.543
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of idiopathic, familial hyperchylomicronaemia in a cat

Abstract: Primary hyperlipoproteinaemia (hyperchylomicronaemia with slight very low density lipoprotein elevation) is described in two related male cats. Fasting hyperlipaemia, lipaemia retinalis and subcutaneous xanthomas were detected on clinical examination. In one cat lipoprotein lipase activity measured after heparin activation was significantly reduced compared to the response in a normal cat. The lipid and protein concentration in each of the lipoprotein classes and the lipoprotein distribution of the two hyperli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 0 publications
1
42
1
Order By: Relevance
“…Members of a naturally occurring, inbred colony of cats presented with chylomicronemia (8), which raised the possibility that these cats may be suffering from LPL deficiency. Biochemical analysis indeed revealed that these cats do have a deficiency of plasma LPL catalytic activity, yet possess normal function of the LPL cofactor, apo CII (9).…”
Section: Introductionmentioning
confidence: 99%
“…Members of a naturally occurring, inbred colony of cats presented with chylomicronemia (8), which raised the possibility that these cats may be suffering from LPL deficiency. Biochemical analysis indeed revealed that these cats do have a deficiency of plasma LPL catalytic activity, yet possess normal function of the LPL cofactor, apo CII (9).…”
Section: Introductionmentioning
confidence: 99%
“…The only well-documented primary lipid disorder in cats is a familial hypertriglyceridaemia, for which clinical signs typically begin at 8 to 9-months-of-age, and respond well to a low fat diet. 7,19,22 Elevations in both cholesterol and triglycerides are consistent with familial primary hypertriglyceridaemia documented in cats, 7 and although triglyceride levels frequently respond well to dietary fat restriction in lipid disorders, cholesterol levels usually do not. 1 Primary hypercholesterolaemia is unreported in cats, and hypercholesterolaemia is typically not associated with xanthoma formation in humans, dogs or cats.…”
Section: Clinicalmentioning
confidence: 88%
“…14,17,[20][21][22] Resolution in this cat was delayed until after 20 weeks on the low-fat diet, however concurrent glucocorticoid therapy was only discontinued 6 weeks prior to resolution, and may have influenced the occurrence of both demodicosis and dermatophytosis, and contributed to the slow resolution of hyperlipidaemia and xanthomas.…”
Section: Clinicalmentioning
confidence: 99%
See 2 more Smart Citations